Evaluasi Proses Bisnis Divisi Material Requirement Planning (MRP) Menggunakan Metode Quality Evaluation Framework (QEF) dan Root Cause Analysis (RCA) (Studi Pada PT. Xacti Indonesia) - Dorothy Gabriel Sihombing; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The progress of digital cameras today is able to attract the interest of people from various circles to buy it. As one of the Original Equipment Manufacturer (OEM) based companies that produce digital cameras, PT. Xacti Indonesia needs to develop business processes that run on the company effectively and efficiently. This study focuses on the evaluation of business processes in the Material Requirement Planning (MRP) division of PT. Xacti Indonesia. The current business process in the MRP division has a number of problems, where when updating the amount of material stock to the system it must take longer than planned and within one week there are still 3 to 4 failures in the system which result in some material data updated by the MRP operator is not stored by the system. Through this research, the author evaluates business processes using the Quality Evaluation Framework (QEF) and Root Cause Analysis (RCA) methods. The QEF method is able to combine various needs related to quality factors (quality factors) and help evaluate business processes objectively, quantitatively, and based on facts. And, the RCA method is used to analyze the root causes that occur in the MRP division process. The results of the MRP division business process evaluation using QEF were found Q12 (Frequency Failure) and Q13 (Time Efficiency) which were not in accordance with the planning, then the results of the appropriate root analysis using RCA with the 5 Analysis Why tool.